1986
DOI: 10.1038/bjc.1986.174
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of iron and iron binding proteins in spleen with reference to Hodgkin's disease

Abstract: Summary The distribution of iron and iron binding proteins (IBP) Hodgkin's disease (HD) is a progressive disorder of' the lymphoid system often accompanied by a deficiency in cell mediated immunity (Hansen & Good, 1974;Kaplan, 1976). The depression of cell mediated immunity in HD has been related to increased activity of suppressor cells (Twomey et al., 1980;Hillinger & Herzig, 1978;Goodwin et al., 1977; Sibbett et al., 1978), the presence of circulating inhibitory factors (Siegal, 1976; Fuks et al., 1976;M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Iron is primarily located in the ferritin core present in the cytoplasm and in the lysosomes present in macrophages in the red pulp. 3941 Although we did not specifically stain for macrophages or ferritin using IHC, iron could be easily localized using Perl’s staining of sections from OCT embedded tissue. Electron dense regions and EDS analysis confirmed the presence of iron in TEM images.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is primarily located in the ferritin core present in the cytoplasm and in the lysosomes present in macrophages in the red pulp. 3941 Although we did not specifically stain for macrophages or ferritin using IHC, iron could be easily localized using Perl’s staining of sections from OCT embedded tissue. Electron dense regions and EDS analysis confirmed the presence of iron in TEM images.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had already focused on the establishment of associations between the immune profile of the infiltrating leukocytes in the tumor and established clinicopathological variables of breast cancer outcome [ 44 46 ] but very few have approached the association with iron-related proteins. Interestingly, Britten et al had already demonstrated that spleens from patients with Hodgink’s disease presented a higher expression of ferritin in macrophages, particularly around tumor nodules [ 47 ]. The present results point to the fact that deregulation of iron metabolism occurs not only at the primary tumor microenvironment, but also in preferential metastatic niches.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not unexpected, given the spleen's role in the reticuloendothelial system. Stainable iron can be present in the normal spleen, and might be predicted to increase in the setting of cirrhosis, which is sometimes accompanied by low‐grade haemolysis . Despite this, in the majority of cases splenic iron was modest.…”
Section: Discussionmentioning
confidence: 99%